Phytochemical Screening, Antioxidant and Antibacterial Evaluations of Two Zingiberaceae Plants - Naiyl1, Rania; I. Ahmed2, Badr Eldin (Gezira Journal of Engineering and Applied Sciences, 2019)
The crude ethanolic extract of two commonly zingiberaceae medicinal plants Zingiber officinale (ginger) and Curcuma longa (turmeric) were screened for their phytochemical content which revealed the presence of alkaloids, glycosides, terpenoids, flavonoids, tannins and saponins